Bodystorming for movement-based interaction design - Segura, Elena; Vidal, Laia; Rostami, Asreen (Human Technology, 2016)
After a decade of movement-based interaction in human–computer interaction, designing for the moving body still remains a challenge. Research in this field requires methods to help access, articulate, and harness embodied experiences in ways that can inform the design process. To address this challenge, this article appropriates bodystorming, an embodied ideation method for movement-based interaction design. The proposed method allows for early consideration of the physical, collocated, and social aspects of a designed activity as illustrated with two explorative workshops in different application domains: interactive body games and interactive performances. Using a qualitative methods approach, we used video material from the workshops, feedback from participants, and our own experience as participants and facilitators to outline important characteristics of the bodystorming method in the domain of movement-based interaction. The proposed method is compared with previous ones and application implications are discussed.